Synthesis of N, F and S co-doped graphene quantum dots - Kundu, Sumana; Yadav, Ram Manohar; Narayanan, T. N.; Shelke, Manjusha V.; Vajtai, Robert; Ajayan, Pulickel M.; Pillai, Vijayamohanan K. (Nanoscale, 2015)
Graphene quantum dots (GQDs) are a promising category of materials with remarkable size dependent properties like tunable bandgap and photoluminescence along with the possibility of effective chemical functionalization. Doping of GQDs with heteroatoms is an interesting way of regulating their properties. Herein, we report a facile and scalable one-step synthesis of luminescent GQDs, substitutionally co-doped with N, F and S, of similar to 2 nm average size by a microwave treatment of multi-walled carbon nanotubes in a customized ionic liquid medium. The use of an ionic liquid coupled with the use of a microwave technique enables not only an ultrafast process for the synthesis of co-doped GQDs, but also provides excellent photoluminescence quantum yield (70%), perhaps due to the interaction of defect clusters and dopants.